Twice : a novel [large type] - Albom, Mitch, 1958- (Good morning America book club., 2025)
"What if you got to do everything in your life -twice? The heart of Mitch Albom's newest novel is a love story that dares to explore how our unchecked desires might mean losing what we've had all along"-- Provided by publisher.